The relative contributions of genetic and non‐genetic factors to the risk of neuroblastoma - Eun Mi Jung; Julia E. Heck; Logan G. Spector (Pediatric Investigation)
ABSTRACT Previous literature has well‐established genetic factors as being associated with neuroblastoma (NB). About 1%–2% of NB cases are familial, with 85% of these cases predisposed to mutations in the PHOX2B and ALK genes. The genetic basis of sporadic NB has been studied through genome‐wide association studies and next‐generation sequencing approaches. Particularly, germline variants, as well as copy number variations, confer increased risks of NB, often with effect estimates ≥1.5, underscoring the strong genetic contributions to NB. However, the strength of the association varied in non‐genetic factors. Some risk factors, such as birth defects, maternal illicit drug use, and early infections, had relatively stronger associations (effect estimates ≥1.5 or ≤0.67), while some other factors remain inconclusive. This suggests that certain non‐genetic factors may play a more prominent role in NB risk, while further research is needed to clarify the impact of others. We synthesized and critically evaluated existing literature on the risk factors of NB to provide an overview, analyze the current state of knowledge, and outline a research path to address the relative contributions of genetic and non‐genetic factors in NB. Future epidemiologic studies should incorporate novel methods for measuring genetic and non‐genetic factors to comprehensively assess the full extent of factors contributing to NB. Furthermore, the utilization of dried blood spots holds promise to overcome technical and recruitment challenges for future studies. These strategies will contribute to a more holistic understanding of NB etiology and potentially lead to improved prevention strategies.